2013
DOI: 10.1126/science.1241396
|View full text |Cite
|
Sign up to set email alerts
|

Abundant Porewater Mn(III) Is a Major Component of the Sedimentary Redox System

Abstract: Soluble manganese(III) [Mn(III)] can potentially serve as both oxidant and reductant in one-electron-transfer reactions with other redox species. In near-surface sediment porewater, it is often overlooked as a major component of Mn cycling. Applying a spectrophotometric kinetic method to hemipelagic sediments from the Laurentian Trough (Quebec, Canada), we found that soluble Mn(III), likely stabilized by organic or inorganic ligands, accounts for up to 90% of the total dissolved Mn pool. Vertical profiles of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
211
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(222 citation statements)
references
References 44 publications
6
211
5
Order By: Relevance
“…The formation of new vacancy sites likely also alters the optical absorption properties of the modified nanosheet (35). Our model, however, requires that the putative interlayer Mn(III) ion lack an optical absorption signature in the 335-to 800-nm range; this could not be verified through published studies of the UV-vis absorption spectra of Mn 3+ because this species is unstable in aqueous solution (11,25). Hole dynamics: Recombination vs. water oxidation chemistry.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The formation of new vacancy sites likely also alters the optical absorption properties of the modified nanosheet (35). Our model, however, requires that the putative interlayer Mn(III) ion lack an optical absorption signature in the 335-to 800-nm range; this could not be verified through published studies of the UV-vis absorption spectra of Mn 3+ because this species is unstable in aqueous solution (11,25). Hole dynamics: Recombination vs. water oxidation chemistry.…”
Section: Discussionmentioning
confidence: 61%
“…Manganese oxide photodissolution in the presence of 10-40 mg/L DOM has been reported to have a 5-10 times greater efficiency (9) than measured here for MnO 2 photoreduction without organics. DOM can increase the accumulation of reduced Mn by acting as the chromophore that either initiates electron transfer to the mineral (9) or photolyzes to generate reactive oxygen species (5); by acting as an electron donor to the photoexcited mineral; or by providing ligands that can complex intermediate Mn 3+ as Mn(III) (aq) species (11). Due to the optical properties of DOM, the first mechanism is only important under UV light, which is a minor component of the sun's irradiance spectrum on the Earth's surface and has a lower penetration depth (up to ∼25 m) in natural waters than visible wavelengths (∼100 m) (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rivers have long been considered as external sources of pollutants (mainly nutrients) in lakes, numerous studies have reported contribution of lake sediments as an internal source of contaminants to overlying waters [32,33]. Lu and Chenga [34] reported that heavy metal accumulation in lake sediments is not always correlated with anthropogenic pollution and is often strongly determined by the local geochemical background.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies (e.g., Canfield et al, 1993a, b;Thamdrup and Dalsgaard, 2000), we assumed that accumulating dissolved Mn was Mn 2+ . This ignores a potential contribution from Mn 3+ , which in some cases can constitute a substantial fraction of the dissolved Mn pool at the upper boundary of the zone with soluble Mn accumulation in marine sediments (Madison et al, 2013). Further studies of the dynamics of soluble Mn 3+ are required to evaluate its potential importance in anoxic incubations.…”
Section: Rate Measurementsmentioning
confidence: 99%